The relationship between liquidity and firm performance of selected public listed companies in Malaysia [2009-2008] / Nurul Fatehah Mohd Yusof - Mohd Yusof, Nurul Fatehah (2019)
The purpose of this study is to examine the relationship between liquidity and firm performance of selected public listed companies in Malaysia. This study is conducted due to financial crisis that often happen for most companies and it eventually effect the performance of the companies itself. Sample of 100 public listed companies in Malaysia were involved in this study. Five variables were used in this study which are current ratio, quick ratio, return on capital employed, firm age and firm size which act as independent variables. Return on asset were used to measure the firm performance which act as dependent variables. The relationship between dependent variables and independent variables were measure from year 2009 until 2018. According to the findings, the result show that only return on capital employed show positive and significant result while other variables show positive but insignificant result